What are you, allusion? - Valotka, Audrius (Lietuvių kalba, 2017)
The article deals with issues of allusion theory and provides “demarcation lines”, i.e. features that allow distinguishing allusion from other types of intertext. Allusion is commonly defined as an indirect, implied, or covert reference, but here it is defined as an element of text which has certain features. This is in line with conventional terminological practice which requires a proper definition to entail a hypernym superordinate by one or two levels. Allusion is intertext, therefore its definition must include the categories of “intertext” or “text”. The essential features of an allusion are the following: a) Allusion is made of two texts: the text in praesentia and the text in absentia. The text in absentia is widely perceived as a work of art, a historical fact, a person, etc. It is always prior, except for Jason Holt’s interpretation of ex ante allusions. b) The texts in absentia and in praesentia are bound by a covert, indirect reference the purpose of which is to link both texts and to establish allusive connection between them. The question whether meta-comments made by the author about the connection distort the allusion remains open. c) The connection between the text in praesentia and the text in absentia is enabled by the same or similar elements, i.e. representants. The elements of the text in praesentia which aggravate the recognition of the text in absentia are transformants. Context may also perform the function of transformants. d) When the text in absentia affects only part of the text in praesentia, such an allusion is referred to as a local allusion. If the internal links of the text in absentia affect the internal links of the text in praesentia, such an allusion is referred to as a structural allusion (extension, imitation, parody, plagiarism). e) From the structural perspective, parody, plagiarism, imitation, and extension are not independent intertexts since they differ from allusions only in their function (i.e. irony, secret copying and open mimicking, respectively), therefore they are considered variations of allusion. f) Allusion is an open, incomplete structure since its meanings are created not only by the author but also by the addressee. If the author and the addressee have common background knowledge, the addressee recognises the allusion and is able to interpret it in accordance with the author’s intention. If the background knowledge of the author and the addressee differ, the addressee does not notice the allusion or she/he interprets it in her/his own way.